Completing sporting sections in high education institutions using the Sport Selection mobile application - Baranaev, Yury A. (University Pedagogical Journal, 2023)
The article is devoted to the importance of choosing a sports section for a firstyear student at the university. The author discusses various problems faced by students, including the lack of proper sports predisposition and the problems of regularity of attending training sessions. It is most effective to focus on anthropometric indicators, motor ability and biological age of students to staff sports sections. It is also important to take into account the interests and preferences of the student. The author propose an approach to the selection of sports sections in the conditions of higher education institution using the mobile application Sport Selection. The solution of questions about the choice of sports section will help students to discover their natural abilities and develop them, learn to achieve their goals, as well as increase motivation to do sports at the university.
Keywords: institutions of higher education; sports sections; mobile application; recruitment; sports suitability; anthropometric characteristics